Service Life Design of Deck Closure Joints in ABC Bridges: Guidelines and Practical Implementation - Jaberi Jahromi, Azadeh; Valikhani, Alireza; Mantawy, Islam M.; Azizinamini, Atorod (Frontiers in Built Environment, 2020)
Closure joints are commonly used in the bridge deck to connect two adjacent prefabricated elements in accelerated bridge construction. The current practice of closure joints utilizes the use of different materials such as normal-strength concrete and ultrahigh performance concrete (UHPC) with the use of different reinforcement details such as straight bars, hooked bars, and headed bars. The design of closure joints to meet the strength limit state is quite simple; however, the design of a service life for these joints is quite challenging. A framework for the service life design of closure joints in bridges, built using accelerated bridge construction techniques, is developed in this paper. This framework includes several steps: (1) identification of project requirements especially those that influence the service life of closure joints; (2) identification and selection of feasible closure joint types suitable for the project requirements; (3) identification of factors that influence the service life of closure joints along with the mode of failures and consequences; (4) identification of suitable approaches or strategies for mitigating failure modes or assessing the risk of damage; (5) modification of closure joint detail using mitigation strategies that may result in the development of several alternatives and options for each closure joint type; (6) estimation and comparison of service life design for each modified alternative using finite or target service life approaches; and (7) conduction of life cycle cost analysis for each modified alternative along with the selection of the optimum closure joint details to meet both strength and service life demand. This framework is used in practical design implementation, for example, the 1,400-ft-long bridge in Boston, MA, United States. Several closure joints details were studied under this research such as the use of normal-strength concrete with straight bars, 180° hooked bars, 90° hooked bars, and headed bars along with the use of ultra-high performance concrete with straight bars. The mitigation strategies for service life design of closure joints include (1) increasing deck and closure joint thickness by 0.5 in. and the use of bottom sealer; (2) the use of 0.5 in. of UHPC overlay and bottom sealers; (3) increasing the deck and closure joint thickness by 0.5 in. and the use of membrane and asphalt overlay along with bottom sealer; and (4) increasing the deck and closure joint thickness by 0.5 in. and the use of stainless steel in deck panels and closure joints. The least life cycle cost is obtained using UHPC overlay and bottom sealers, and the use of UHPC in closure joints leads to a reduction in repair intervals. This paper summarizes the outcome of the design for the service life of those closure joints comparatively.